Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/bc500215m
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Antiviral XTEN–Peptide Conjugates with Long in Vivo Half-Life and Enhanced Solubility

Abstract: XTENs are unstructured, nonrepetitive protein polymers designed to prolong the in vivo half-life of pharmaceuticals by introducing a bulking effect similar to that of poly(ethylene glycol). While XTEN can be expressed as a recombinant fusion protein with bioactive proteins and peptides, therapeutic molecules of interest can also be chemically conjugated to XTEN. Such an approach permits precise control over the positioning, spacing, and valency of bioactive moieties along the length of XTEN. We have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…However, peptide-based drugs generally suffer from short half-lives due to proteolytic degradation and fast renal clearance, rendering higher doses and frequent injections necessary, which negatively affects patient compliance (2). To improve their pharmacological properties, peptides have been chemically modified by conformational restriction (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) to increase potency and reduce proteolysis, and also by lipidation (14)(15)(16), polymer conjugation (17)(18)(19)(20)(21)(22)(23), and protein fusion (24)(25)(26) to decrease renal clearance. Although these latter conjugates can have enhanced circulatory half-lives, they often suffer from reduced potency and, as a result, require injection of relatively large quantities of the modified peptides.…”
mentioning
confidence: 99%
“…However, peptide-based drugs generally suffer from short half-lives due to proteolytic degradation and fast renal clearance, rendering higher doses and frequent injections necessary, which negatively affects patient compliance (2). To improve their pharmacological properties, peptides have been chemically modified by conformational restriction (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) to increase potency and reduce proteolysis, and also by lipidation (14)(15)(16), polymer conjugation (17)(18)(19)(20)(21)(22)(23), and protein fusion (24)(25)(26) to decrease renal clearance. Although these latter conjugates can have enhanced circulatory half-lives, they often suffer from reduced potency and, as a result, require injection of relatively large quantities of the modified peptides.…”
mentioning
confidence: 99%
“…Some studies have reported on the application of MMT and OMMT in PVAc, but they all need other additives or agents as main components that are necessary in their synthesis, such as poly(vinyl pyrrolidone), 18,19 anionic surfactants, 20 polyvinyl alcohol, 21,22 glycidyl methacrylate, 23,24 and high-density polyethylene. 25,26 Adding an additional component means adding one or more procedures that makes the synthesis or preparation more complex and so should be avoided. Furthermore, OMMT has some organic properties that are determined by the organics intercalated into MMT layers, [27][28][29] so it has the advantages of inorganic and organic properties.…”
mentioning
confidence: 99%
“…The conjugates contain multiple copies of T‐20 attached to a single XTEN polymer, but instead of traditional end‐to‐end fusion, the T‐20 molecules are attached at various positions along the XTEN sequence through the side‐chains of Cys residues. Investigation of the PK properties of the most active conjugate (named T‐20‐XTEN‐4) following s.c. administration to Sprague–Dawley rats revealed an elimination half‐life of 55.7 h, corresponding to a 20‐fold increase relative to the reported half‐life of unmodified T‐20 …”
Section: Recombinant Peg Mimeticsmentioning
confidence: 86%